What’s Wrong with Gazanias? A Review of the Biology and Management of Weedy Gazania Species - Babar Shahzad; Muhammad Adnan; Ali Ahsan Bajwa (Plants)
Gazania is a genus of herbaceous plants from the Asteraceae (daisy) family. Native to southern Africa, several species of this genus have been introduced to different countries as ornamental garden plants due to their beautiful flowers. In the wild, Gazania species have been observed with flowers of different shades of pink, red, yellow, orange and combination of these colours. Some species of Gazania have escaped the gardens and become highly invasive weeds in their introduced range. Invasive, drought-tolerant and prolific seed-producing Gazania plants are found in Australia, New Zealand, Algeria, Egypt, Europe and California. In particular, two perennial species, Gazania linearis and Gazania rigens, commonly known as gazania, have become a major problem in Australia. They have naturalized and are widespread in a range of environments, such as roadsides, pasture/grassland systems, coastal sand dunes, and natural and managed ecosystems. Their seeds and underground reproductive structures are carried along roadsides by slashers, machinery, wind and water, and spread into native vegetation, pastures, horticultural crops and broadacre agronomic crop production systems. Gazania causes significant environmental, production and economic losses in the infested ecosystems. While limited research has been conducted on their biology and invasion ecology, anecdotal evidence suggests that the ability of gazania plants to produce a large number of seeds form thick, dense populations, and tolerate harsh environments, including drought, heat and sub-optimal soil pH, making them persistent, problematic weed species. In addition, perennial growth habit, high genetic diversity and allelopathic potential have also been suggested to facilitate their invasion success, but no research has been conducted on these aspects. Gazania is very difficult to manage, and currently, there are no effective control options available, including chemical herbicides. The lack of knowledge on their biology, invasion pathways and management is hindering the effective management of gazanias. This review compiles and synthesizes currently available information on the distribution, biology, ecology and management of weedy gazania species, with a particular focus on Australia. We also highlight the key knowledge gaps for future research. We believe this information provides researchers and practitioners with an up-to-date account on the weedy aspects of these popular ornamental plants and will help improve management efforts.